Role of Annealing Temperature in Tuning Magnetic Properties of Fe-Co-Al2O4 Spinel Aluminates - Poongodi, R.; Senguttuvan, S.; Sagayaraj, R. (Asian Journal of Chemistry, 2023)
The annealing temperature (600, 700, 800, 900, 1000 ºC) can have a significant effect on the microstructure, surface functionalization, surface morphology and magnetic properties of the Fe-Co-Al2O4 spinel aluminates synthesized by the coprecipitation method. Increasing the annealing temperature leads to a change in the crystalline structure of the spinel aluminates, resulting in different physical and magnetic properties. By controlling the annealing temperature, it is possible to obtain improved structural stability, higher crystallinity and better magnetic properties of the Fe-Co-Al2O4 spinel aluminates. The annealing temperature also affects the microstructure and morphology of the spinel aluminates, resulting in different XRD patterns, FTIR spectra and FE-SEM images. As a result, affects the crystallite size (D: 9.49 to 14.25 nm), lattice constant (a: 8.1506 to 8.2889 Å) and surface area of the spinel aluminates, resulting in different anisotropy constant (K: 33.06 to 66.48 J/m3) values. The VSM study showed that higher annealing temperatures have a positive effect on the magnetic properties of Fe-Co-Al2O4 samples. The increased magnetization capacity of these samples can be attributed to the multi-domain nature of their crystallites, which allows for better magnetic moment ordering and improved magnetization performance (Ms: 45.421 × 10-3 to 0.13635 emu/g). At higher temperatures, more atoms were able to move and reorient themselves, resulting in higher coercivity (Hc: 391.75 to 873.02 Oe), magnetic moment (μB: 0.0029 to 0.007 μB Tesla) and Remnant ratio (R: 0.4113 to 0.4570 no unit) values.